Awareness and Attitude Regarding Cervical Cancer Screening among Reproductive Age Women - Baral, Pramila; Pokharel, Jyotsana; Gachhadar, Rashmi (Journal of Nepal Health Research Council, 2020)
Background: Cervical cancer is preventable so awareness can be as effective as any other method to prevent it.The study aims to assess awareness and attitude regarding cervical cancer screening among reproductive age women in a tertiary level hospital, Kathmandu, Nepal.Methods: A descriptive cross sectional study was carried out among 170 reproductive age women attending Nepal Medical College Teaching Hospital using purposive sampling technique. A semi structured interview schedule was used to collect data via face to face interview. Data was summarized using frequency, percentage, mean and standard deviation. Multiple logistic regression was used to determine the factors associated with awareness and attitude.Results: Among 170 reproductive age women, mean age was 31.49 ± 8.70 years. Majority 151 (88.8%) of the women had heard of cervical cancer while 119 (70%) of them had heard about cervical cancer screening. Among them, only 17 (11.3%) had adequate awareness regarding cervical cancer screening. Seventy five (46.6%) of the women had positive attitude towards cervical cancer screening. Employment status [95% CI (0.01-0.38), AOR=0.06, p=0.003] was associated with awareness whereas, ethnicity, employment status and marital status were associated with attitude.Conclusions: Most of the women were unaware about the cervical cancer screening but nearly half of the respondents had positive attitude. Therefore it is very crucial to provide health education and awareness through supervised client education. Focused group discussion as an effective approach of awareness program can be conducted in order to include specific group such as unemployed and unmarried women.Keywords: Attitude; awareness; cervical cancer; reproductive age women; screening